السلطنة والخلافة في الدولة العثمانية من حيث النظرية والتطبيق - غومة, مبروكة عبد السلام (Tobruk University Journal of Social and Human Sciences, 2024)
This research deals with the sultanate and the sultanate in  the ottoman political system between their real concept and how they are related, and the development of the concept of the caliphate between its original conditions until it reached the Omanis and knowing how the Omanis adopted this system and dealt with it in line with the ottoman policy , so that it affected the validity of its application after the succession of this transfer aluminum among the former nations , to reach of succession from an ottoman perspective And what Ottoman Caliphate , achieved . or rather , what it gained for the Ottomans in terms of a characteristic that enabled them to tighten their control over the Islamic nations , after their successive conquests of the Arab countries , especially  the Hijaz and Egypt , all the way to North Africa .